Eviota nigramembrana, a new dwarfgoby from the Western Pacific (Teleostei: Gobiidae) - Greenfield, David W.; Suzuki, Toshiyuki (Zootaxa, 2013)
Eviota nigramembrana is described from the Ryukyu Islands, Japan and also recorded from the Philippine Islands. It be-longs to the cephalic sensory-pore system pattern group I (complete), has a dorsal/anal fin-ray formula of 8/8, 5th pelvic-fin ray absent, some lower pectoral-fin rays branched, five dark internal bands between anal-fin origin and caudal fin, no distinct marking on pectoral-fin base, dark internal rectangular mark above midline of ural centrum, a light spinous dorsal fin, and black pigment on the opercular membrane.